IL-21 and IL-21 receptor in the immunopathogenesis of multiple sclerosis. (3rd May 2016) - Ghalamfarsa, Ghasem; Mahmoudi, Mahmoud; Mohammadnia-Afrouzi, Mousa; Yazdani, Yaghoub; Anvari, Enayat; Hadinia, Abolghasem; Ghanbari, Amir; Setayesh, Maryam; Yousefi, Mehdi; Jadidi-Niaragh, Farhad
Abstract: Cytokines are considered important factors in the modulation of various immune responses. Among them, interleukin (IL)-21 is one of the major immune modulators, adjusting various immune responses by affecting various immune cells. It has been suggested that IL-21 may enhance autoimmunity through different mechanisms, such as development and activation of helper T (TH )-17 and follicular helper T (TFH ) cells, activation of natural killer (NK) cells, enhancing B-cell differentiation and antibody secretion and suppression of regulatory T (Treg ) cells. Moreover, IL-21 has also been suggested to be an inducer of autoimmunity when following treatment of MS patients with some therapeutics such as alemtuzumab. This review will seek to clarify the precise role of IL-21/IL-21R in the pathogenesis of MS and, in its animal model, experimental autoimmune encephalomyelitis (EAE).